2009
DOI: 10.1186/1477-7525-7-39
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in patient burdens with graphical computerized adaptive testing on the ADL scale: tool development and simulation

Abstract: Background: The aim of this study was to verify the effectiveness and efficacy of saving time and reducing burden for patients, nurses, and even occupational therapists through computer adaptive testing (CAT).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
51
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(60 citation statements)
references
References 12 publications
7
51
2
Order By: Relevance
“…As a result, the test length of CAT was about 58% that of NAT, a little higher than in previous studies with about half the test length [1,9-11]. …”
Section: Discussioncontrasting
confidence: 53%
“…As a result, the test length of CAT was about 58% that of NAT, a little higher than in previous studies with about half the test length [1,9-11]. …”
Section: Discussioncontrasting
confidence: 53%
“…This advantage was previously demonstrated in a simulation study of the Activities of Daily Living CAT, which found that the CAT provided similar results to a static version while reducing the number of items administered by 50%. 31 Results from other studies indicate that scores similar to those obtained with full-length item banks (ranging in length from 18 -585 items) can be achieved through much shorter CATs when measuring functional status, [32][33][34] mental health status, 21,27,35,36 or the impact of conditions, such as headache, 23,37 diabetes, 30 chronic pain, 28 and asthma. 29 Most actual CAT applications used between 5 and 7 items to measure 1 construct.…”
Section: Respondent Burdenmentioning
confidence: 86%
“…Many studies [3943] have reported that item response theory (IRT)-based computer adaptive testing (CAT) has the advantages of both long-form and short-form questionnaires [4446] in precision and efficiency. Many employees already own mobile phones.…”
Section: Discussionmentioning
confidence: 99%